PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN WISATAWAN UNTUK BERKUNJUNG KE DAYA TARIK WISATA LADAYA KUTAI KARTANEGARA - Ria Rahim (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
This study aims to determine the variables consisting of advertising, public relations and direct marketing have a simultaneous and partial effect on the decision of tourists visiting Ladaya Tenggarong Kutai Kartanegara. This study used two variables, namely the promotion mix and the visiting decision. This type of research is quantitative, the population of 282,424 with a sample of 100. Data collection techniques: field research observations, interviews, questionnaires, and library research. Then the analysis technique used is linear regression using the test: validity test, reliability test, class assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear analysis. The results obtained in this study are promotion mix variables consisting of advertising, public relations and direct selling simultaneously influence the decision to visit the tourist attraction of Ladaya Kutai Kartanegara. The promotional mix variable consisting of advertising, public relations and direct sales partially influences the tourist's decision to visit the Ladaya Kutai Kartanegara tourist attraction.